Demographics and Awareness of Pag-Ibig Fund’s E-Government Service Among Private Employees in the Philippines - Masinas, Annah Erania; Marbibi, Joyce Anne T. Pini; Buena, Mae Michelle; Vigonte, Florinda; Malang, Bernandino P.; Abante, Marmelo V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
E-government is gaining prominence, and more research is being conducted on the topic. This study aims to find out how familiar people are with e-government services, why they use or don't use them, and if there is a significant link between demographics and client awareness of e-governance Pag-IBIG Fund offers. A survey using Google forms was carried out to obtain the necessary information on the individuals working for Mang Inasal in Nueva Vizcaya. The study analyzed 191 replies to discover the characteristics that influenced their awareness and use of Pag-IBIG Fund's e-government services. Contrary to what has always been assumed, 71.2% of the respondents are aware of the E-Government services offered by Pag-IBIG Fund - this number shows a formidable familiarity among the people of Mang Inasal in Nueva Vizcaya. Using Spearman’s Correlation and analysis, it also indicated that there is no significant relationship between age (p=.247), educational degree (p=.391), and Income (p=.113) over the awareness of the E-Government Services offered by Pag-IBIG Fund. These insights should be helpful to academics, professionals, and decision-makers.